Synchronization as a biological, psychological and social mechanism to create common time: A theoretical frame and a single case study - Bao, Yan; Pöppel, Ernst; Wang, Lingyan; Lin, Xiaoxiong; Yang, Taoxi; Avram, Mihai; Blautzik, Janusch; Paolini, Marco; Silveira, Sarita; Vedder, Aline; Zaytseva, Yuliya; Zhou, Bin (PsyCh journal, 2015)
Synchronizing neural processes, mental activities, and social interactions is considered to be fundamental for the creation of temporal order on the personal and interpersonal level. Several different types of synchronization are distinguished, and for each of them examples are given: self-organized synchronizations on the neural level giving rise to pre-semantically defined time windows of some tens of milliseconds and of approximately 3 s; time windows that are created by synchronizing different neural representations, as for instance in aesthetic appreciations or moral judgments; and synchronization of biological rhythms with geophysical cycles, like the circadian clock with the 24-hr rhythm of day and night. For the latter type of synchronization, an experiment is described that shows the importance of social interactions for sharing or avoiding common time. In a group study with four subjects being completely isolated together for 3 weeks from the external world, social interactions resulted both in intra- and interindividual circadian synchronization and desynchronization. A unique phenomenon in circadian regulation is described, the "beat phenomenon," which has been made visible by the interaction of two circadian rhythms with different frequencies in one body. The separation of the two physiological rhythms was the consequence of social interactions, that is, by the desire of a subject to share and to escape common time during different phases of the long-term experiment. The theoretical arguments on synchronization are summarized with the general statement: "Nothing in cognitive science makes sense except in the light of time windows." The hypothesis is forwarded that time windows that express discrete timing mechanisms in behavioral control and on the level of conscious experiences are the necessary bases to create cognitive order, and it is suggested that time windows are implemented by neural oscillations in different frequency domains.
Keywords: Circadian Rhythm; social interaction; longitudinální studie; vnímání času; beat phenomenon; Time Factors; cirkadiánní rytmus; discrete time; interpersonální vztahy; Interpersonal Relations; mužské pohlaví; desynchronization; Models, Biological; Humans; Time Perception; time window; časové faktory; circadian rhythm; biologické modely; Longitudinal Studies; synchronization; lidé; Male